Optimalisasi Program Tanggap Stunting dengan Pangan Aman dan Sehat di Kota Bandung dalam Perspektif Smart City - Supi Ainul Lutpi; Nanang Suparman; Sakrim Miharja (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
In order to improve public services, the City of Bandung as one of the cities in Indonesia that has implemented a smart city is increasingly trying to optimize its services, including health services, one of which is in dealing with the problem of stunting. Where in 2020, the stunting rate in the city of Bandung increased to 8.86%. To that end, the Bandung City government created the Bandung Tanginas program (Tanggap Stunting Dengan Pangan Aman Dan Sehat) which is a program aimed at enabling the City of Bandung to become a City with Zero News Stunting. Therefore, the goal to be achieved in this research is to find out how to optimize the Tanginas Program in Bandung City from a Smart city Perspective. This research is descriptive with a qualitative approach. The results of this study indicate that the optimization of the Tanginas program in the city of Bandung seen from the smart city perspective is still not optimal. This is based on the limited amount of healthy food intake, population density, lack of green open space and the lack of use of information technology.